Serological diagnostic of maedi-visna (MVV) in sheep and caprine arthritis encephalitis virus (CAEV) in goats in Macedonia - Mitrov Dine; Naletoski Ivanco; Acevski Sinisa; Dzadzovski Igor; Krstevski Kiril; Ulcar Igor; Celeska Irena (Macedonian Veterinary Review, 2009)
Maedi-Visna in sheep and CAEV in goats are diseases caused by lentiviruses with very similar antigenic characteristics. This diseases are very important for the animal husbandry because of the economical losses they cause (reduced milk yield, lower body weight, deaths, therapy expenses). The results in this article, represents the first serological confirmation for the existence of this diseases in Macedonia. Investigations showed high percent of seroprevalence in the examined herds. The seroprevalence ranges from 60.3% for Maedi-Visna to 55.8% for CAEV. Despite the presence of clinical signs of the disease, the mortality is low, witch is related to the presence of the causal agent in the field i.e. the endemic character of this diseases.